2012
DOI: 10.4172/2155-9880.1000217
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Reduces Left Ventricular Eccentric Re-modeling In Experimental volume Overload in the Rat

Abstract: Aims: Left ventricular hypertrophy (LVH) is often associated with a change in myocardial energy substrate preference from fatty acids to glucose. A possible antihypertrophic treatment strategy could aim at stimulating or restoring normal myocardial energy metabolism. Metformin, an adenosine monophosphate-activated protein kinase (AMPK) activator used in the management of glucose metabolism in diabetes, is also a fatty acid oxidation stimulator. The effect of metformin on the development of eccentric LVH and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 27 publications
1
12
1
Order By: Relevance
“…We have recently reported this shift in substrate uptake in 8-week AR animals. 25 We observed that myocardial glucose uptake was increased, whereas fatty acid was reduced in those animals. The overall myocardial oxidative capacity remained unchanged.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…We have recently reported this shift in substrate uptake in 8-week AR animals. 25 We observed that myocardial glucose uptake was increased, whereas fatty acid was reduced in those animals. The overall myocardial oxidative capacity remained unchanged.…”
Section: Discussionmentioning
confidence: 52%
“…32 We have recently shown in the same animal model that LV remodeling can be influenced by diet manipulation and by drugs, such as metformin and fenofibrate, which have significant metabolic effects, whereas lacking any hemodynamic effects. 17,25 This suggests that manipulating myocardial metabolism without hemodynamic effects can impact LV remodeling in AR.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously showed that eccentric LVH caused by severe AR was associated with a shift in energy substrates preference from fatty acids to glucose [ 14 , 15 , 21 ]. Hydroxyacyl-Coenzyme A dehydrogenase (HADH) was reduced in AR animals (Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that a synergy between hemodynamic overload, diet and hypertrophy which are all pro-hypertrophic factors exist but the mechanisms for the increased hypertrophy in AR rats fed with the HF diet remain unclear. We observed in the past that the Erk 1/2 and Stat3 pathways are activated in AR [ 14 , 15 , 33 ]. We did not observe such an activation for the Akt/mTOR pathway in the short protocols (8 weeks) but we did in longer ones (current and [ 34 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation